2011
DOI: 10.1158/0008-5472.can-11-2127
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Immunotherapeutic Targeting of the SSX Family of Cancer–Testis Antigens in Prostate Cancer

Abstract: Recent U.S. Food and Drug Administration approval of the first immunotherapy for prostate cancer encourages efforts to improve immune targeting of this disease. The synovial sarcoma X chromosome breakpoint (SSX) proteins comprise a set of cancer-testis antigens that are upregulated in MHC class I-deficient germline cells and in various types of advanced cancers with a poor prognosis. Humoral and cell-mediated immune responses to the SSX family member SSX2 can arise spontaneously in prostate cancer patients. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 44 publications
5
67
0
Order By: Relevance
“…This was evaluated in a system we have previously reported using a plasmid DNA vaccine encoding the tumor associated cancer-testis antigen SSX2 (Synovial Sarcoma, X Breakpoint 2), 27 relevant HLA-A2 transgenic mice that permit analysis of epitope specific immunity, and a syngeneic tumor cell line model engineered to express the antigen of interest. [28][29][30] We found that MIP-SSX2 immunization elicited greater frequencies of tetramer positive CD8 T cells and antigen-specific IFNg responses, as others have previously reported with minicircles. However, we observed that while MIP-SSX2 protected against tumor challenge in a prophylactic setting, there was a paradoxical loss of antitumor effect following treatment of established tumors.…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…This was evaluated in a system we have previously reported using a plasmid DNA vaccine encoding the tumor associated cancer-testis antigen SSX2 (Synovial Sarcoma, X Breakpoint 2), 27 relevant HLA-A2 transgenic mice that permit analysis of epitope specific immunity, and a syngeneic tumor cell line model engineered to express the antigen of interest. [28][29][30] We found that MIP-SSX2 immunization elicited greater frequencies of tetramer positive CD8 T cells and antigen-specific IFNg responses, as others have previously reported with minicircles. However, we observed that while MIP-SSX2 protected against tumor challenge in a prophylactic setting, there was a paradoxical loss of antitumor effect following treatment of established tumors.…”
Section: Introductionsupporting
confidence: 84%
“…We first constructed a DNA minicircle (DMC-SSX2) by cloning the expression cassette of pTVG-SSX2 (a plasmid encoding the cancer-testis antigen SSX2 that we have previously described) 30,31 into a minicircle production vector (Figs. 1A and B).…”
Section: Resultsmentioning
confidence: 99%
“…CTAs are restricted in normal tissues to germ cells of the testis, with occasional expression in female reproductive organs, and are expressed in histologically different types of malignant human tumors [1][2][3][4]. The tumor restricted expression pattern of CTAs makes them an interesting target for immunotherapeutic approaches [3,5]. The role of CTA expression in tumor cells remains unclear, and thus is an area of active research.…”
Section: Introductionmentioning
confidence: 99%
“…35 Lethe et al 36 reported that expression of MAGE-A1 was observed in 10.8% of carcinoma samples, whereas multi-MAGE-A and NY-ESO-1/LAGE-1 stained 85.9% and 84.8% of samples using immunohistochemistry, suggesting that a panel of CTAs rather than individual ones maybe more valuable as biomarkers. Recently, Smith et al 37 showed that SSX protein expression was restricted mainly to metastatic prostate cancer and not expressed in any primary prostate cancer using immunohistochemistry.…”
Section: Ctas As Potential Biomarkers In Prostate Cancermentioning
confidence: 99%